1996
DOI: 10.1111/j.1749-7345.1996.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mammalian Growth Hormone‐Releasing Hormone Increases Serum Growth Hormone Levels and Somatic Growth at Suboptimal Temperatures in Tilapia

Abstract: The effects of a mammalian growth hormone‐releasing hormone (GHRH), PrebGRF(1–78)OH (bGHRH), on growth and serum growth hormone (GH) levels were investigated in tilapias Oreochromis mossambicus andO. niloticus × O. aureus. Fish were injected intramuscularly or implanted intramuscularly (Silastic or cholesterol implants) with distilled water, 0.1 μg/kg bGHRH, 1.0 μg/kg bGHRH, 10.0 μg/kg bGHRH, or 100.0 μg/kg bGHRH and compared to untreated controls, fish implanted with 60 mg/kg 17α‐methyltestosterone (MT), or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 101 publications
2
6
0
1
Order By: Relevance
“…The failure of bGH or homologous rypGH treatment to promote growth in yellow perch is in contrast to other fish species in which exogenous GH treatment markedly stimulates growth under both optimal (Weatherley and Gill, 1987;Skyrud et al, 1989;Silverstein et al, 2000;Hunt et al, 2000) and sub-optimal (Adelman, 1977;Kelly et al, 1996;Leedom et al, 2002) rearing conditions. Further, the GH treatments induced no increase in IGF-I levels in our studies, as has been shown in several other fish species (Cao et al, 1989;Funkenstein et al, 1989;Moriyama, 1995;Moriyama et al, 1995;Shamblott et al, 1995).…”
Section: Discussionmentioning
confidence: 65%
“…The failure of bGH or homologous rypGH treatment to promote growth in yellow perch is in contrast to other fish species in which exogenous GH treatment markedly stimulates growth under both optimal (Weatherley and Gill, 1987;Skyrud et al, 1989;Silverstein et al, 2000;Hunt et al, 2000) and sub-optimal (Adelman, 1977;Kelly et al, 1996;Leedom et al, 2002) rearing conditions. Further, the GH treatments induced no increase in IGF-I levels in our studies, as has been shown in several other fish species (Cao et al, 1989;Funkenstein et al, 1989;Moriyama, 1995;Moriyama et al, 1995;Shamblott et al, 1995).…”
Section: Discussionmentioning
confidence: 65%
“…Control groups were injected only with 5% ethanol/95% saline solution. In previous studies, injection of 1-100 lg MT per gram body weight into fish body has been shown to affect gonadal development and induce female-to-male sex inversion (Kelly et al, 1996;Sarter et al, 2006;Tan-Fermin et al, 1994). When different doses of MT (0, 1, 10 and 100 lg/g body weight) were injected into female yellow catfish, the levels of 17b-estradiol (E2) and 11-ketotestosterone (11-KT) in the blood were measured using the fish E2 ELISA Kit and 11-KT ELISA Kit (Enzyme-linked Biotechnology Company, Shanghai) as described previously (Parikh et al, 2006).…”
Section: Experimental Animals and Hormone Treatmentmentioning
confidence: 96%
“…It has been reported that synthetic human growth hormone-releasing hormone (h-GHRH) (Peter et al 1984) and bovine GHRH (bGHRH) (Kelly et al 1996a) stimulate GH release in vivo in teleost fish. To date, common carp Cyprinius carpio.…”
Section: Mammalian Growth Hormone-releasing Hormone Indirectlymentioning
confidence: 99%
“…sockeye salmon Oncorhynchus nerka and the Thai catfish Clarias macrocephalus GHRH have been sequenced (Vaughan et al 1992;Parker et al 1993;McRory et al 1995). Various GHRHs have been shown to stimulate GH secretion by increasing plasma GH levels in goldfish Carassius auratus (Peter et al 1984) and the Mozambique tilapia Oreochromis mossambicus (Melamed et al 1995;Kelly et al 1996a) and have stimulated GH release from pituitary cells of goldfish (Vaughan et al 1992), rainbow trout Oncorhynchus mykiss (Luo and McKeown 1989, 1991a, 1991bLuo et al 1990) and the Mozambique tilapia (Melamed et al 1995). Le Bail et al (1991) were able to demonstrate GH release from the pituitary cells of the chinook salmon Oncorhynchus tshawytscha utilizing a h-GHRH, however, goldfish pituitaries were unresponsive to this peptide .…”
Section: Mammalian Growth Hormone-releasing Hormone Indirectlymentioning
confidence: 99%
See 1 more Smart Citation